2009
DOI: 10.1111/j.1525-139x.2009.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond The Current Paradigm: Recent Advances in The Understanding of Sodium Handling – Guest Editors: Stanley Shaldon and Joerg Vienken: Reducing Sodium Intake in Hemodialysis Patients

Abstract: A low salt diet is beneficial for the whole population but has particular advantages for hemodialyis patients because of the role of salt restriction in the management of hypertension and interdialytic weight gain (IDWG). Education on dietary salt intake based on general healthy eating guidelines, such as the "DASH-sodium" diet, should be provided for staff, families, and carers as well as patients. Anuric hemodialysis patients will need to take in approximately 1 l of water for every 8 g salt consumed. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 9 publications
1
78
0
6
Order By: Relevance
“…Using a patient's predialysis SNa as a reference to prescribe individualized or tailored DNa has thus been considered rational (3,10,11), and various prospective interventional trials have found a significant decrease in IDWG by reducing DNa (10,12). As a result of previous guidelines and recommendations (8,9,13) and recent observational studies and commentaries (7,14,15), DNa tailoring may become routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a patient's predialysis SNa as a reference to prescribe individualized or tailored DNa has thus been considered rational (3,10,11), and various prospective interventional trials have found a significant decrease in IDWG by reducing DNa (10,12). As a result of previous guidelines and recommendations (8,9,13) and recent observational studies and commentaries (7,14,15), DNa tailoring may become routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Additional sodium can also be removed by diffusive transport if the dialysate sodium (DNa) level is set below the predialysis serum sodium (SNa) concentration (2,3). Vice versa, higher DNa levels translate into higher dialysate-toSNa gradients, which are associated with thirst (3,4), interdialytic weight gain (IDWG) (5-7), and hypertension (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Is it feasible to lower the dietary salt intake of the average dialysis patient to the level as recommended by guidelines [17,55] ? Buying low-sodium products can be challenging, since sodium is added to nearly all manufactured foods [56] .…”
Section: Dietary Sodium Restrictionmentioning
confidence: 99%
“…Advanced renal failure typically results in sodium retention [1,2,3,4] and hypertension [5,6,7,8,9,10]. Modern renal replacement therapy removes sodium by means of convection/ultrafiltration, as well as by diffusion/dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Modern renal replacement therapy removes sodium by means of convection/ultrafiltration, as well as by diffusion/dialysis. Despite complex processes at the dialysis membrane, the patient plasma sodium (PNa) concentration at the end of dialysis approximates the dialysate sodium (DNa) level [10]. The difference between DNa and PNa may be labeled the ‘sodium gradient’.…”
Section: Introductionmentioning
confidence: 99%